"Bright Side": Margaret Atwood's Post-Apocalyptic Post-Anthropocentrism - Skibo-Birney, Bryn (2017)
Barbara Hill Rigney has described the project of Margaret Atwood's fiction as "a moral issue. …it is the responsibility of the writer/artist not only to describe her world, but also to criticise it, to bear witness to its failures, and, finally, to prescribe corrective measures - perhaps even to redeem" (1). The moral responsibility of the author is evident in Atwood's speculative fiction trilogy, in which the author's known concern for the environment and wildlife conservation provides the impetus to the trilogy's biological catastrophe. Though Atwood describes herself as a "pessimistic pantheist," nevertheless, her post-apocalyptic story-world is not without hope (Atwood, para. 3). Indeed, Atwood describes her speculative America - initially overwhelmed with environmental crises, mass extinctions, rampant poverty and greed, social anarchy, and political corruption before a human-designed global pandemic wipes out most of the human species - as an "ustopia" (utopia and dystopia, together). The utopian hope is embodied within the genetically modified Crakers, human-animal-plant hybrids who live in harmony with their post-apocalyptic environment. Much has been made about the Crakers themselves - whether they are "quasi-humans," or "transgenic monsters" with "primitive brains," or "noble savages" (Atwood 2013, 91; Howells 163, 171; Jameson, para. 5). Zhange Ni provides an insightful reading of Atwood's "radical hope" postulated in the pagan theology of Flood and the nascent mythology of the Crakers in MaddAddam. This paper extends Ni's reading to argue that the characters of the Crakers and the narrative structure of MaddAddam dramatize Atwood's search for the "third thing," a productive and harmonious hybrid alternative to the false binary of innocent passivity and violent activity (Gibson, 26). This "third thing" is essentially a recognition of the power of personal responsibility to enact positive change and it is so prevalent in Atwood's work as to become a narrative structuring device, leading to her characteristic blurred binaries. MaddAddam specifically addresses and blurs the entrenched human-animal binary, which is conventionally linked to human exceptionalism, animal rights abuses, and environmental degradation. Through a combined theoretical approach, using Euro-American philosophers such as Jacques Derrida and Donna Haraway alongside Anishinaabe philosophers like Lawrence Gross, Basil Johnston, and Edward Benton-Banai, this paper reads MaddAddam's narrative structure, pantheistic mythology, and characters as an "ustopian" critique of North America's current failures, and a prescription of specifically post-humanist and post-anthropocentric "corrective measures." Ignoring this advice, the novel warns, invites an inevitable dystopian future, or a utopia, but one devoid of humans.